Spots feathers and curly tails - Tafuri, Nancy (New York : Greenwillow Books, 1988)
Questions and answers highlight some outstanding characteristics of farm animals, such as a chicken's feathers and a horse's mane.
Primary
600-699
Keywords: Domestic animals -- Juvenile literature; Domestic animals; Questions and answers